Significance of CD133 Expression in Invasive Ductal Carcinoma of the Breast - Ahmed, Nagwa Abd El-Sadek; Mohammed, Maisa Hashem (Asian Pacific Journal of Cancer Biology, 2022)
Background and Aim: Cancer stem cells (CSCs) are thought to be responsible for tumor initiation, progression, and resistance to chemotherapy and radiotherapy. CD133 is a trans-membrane glycoprotein which is considered as a putative CSCs marker. Emerging evidence suggests that CD133 may be a critical factor in tumor development, progression and metastasis. The aim of this study was to evaluate the expression of CD133 in mammary infiltrating ductal carcinoma (IDC), and to correlate its expression with some known clinicopathological parameters. Methods: Fifty patients with mammary IDC who underwent modified radical mastectomy were included in this study. From each specimen, two tissue sections were obtained; one was stained by hematoxylin and eosin (H&E) stain to determine the histologic subtype, grade and indicators of local aggressiveness. The second tissue section was immunohistochemically stained by anti-human CD133 antibody. Results: The study revealed statistically significant associations between CD133 expression and poorly differentiated, advanced stage tumors with poor Nottingham Prognostic Index (NPI), triple negative phenotype, lymphovascular invasion (LVI) and lymph node metastasis (LNM). Conclusion: The current study revealed that CD133 is strongly associated with poor prognostic indices; it is positively correlated to poorly-differentiated tumors with high histologic grade and advanced stage